IDENTIFIKASI KARAKTERISTIK DAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG PROGRAM JKN DI RW 2 KELURAHAN MOJOLANGU KOTA MALANG - Dewiyani, Anak Agung Istri Citra; Fadila, Rizki (Politeknik Kesehatan Kemenkes Malang, 2024)
Background: The level of public knowledge about the JKN program is still lacking. The lack of knowledge means that there are still people who are not yet JKN participants or people who are already JKN participants but do not know the benefits of the JKN program. Based on research, several factors influence a person's level of knowledge, both internal and external to the person. Subjects and Method: This is a quantitative analytic study with a cross-sectional approach. Samples were taken by non-randomized sampling using quota sampling of 180 respondents. This study used univariate and bivariate analyses. Results: The research results showed that the majority of respondents had a good level of knowledge about the JKN program (75.6%). The determinant factors related to this knowledge are educational factors (p-value: 0.00) and the role of JKN cadres (p-value: 0.049). Conclusion: From this research, the recommendation that can be given to BPJS Health is to increase the participation of JKN cadres as a means of providing education to the public regarding the JKN program.